2001
DOI: 10.1034/j.1600-0528.2001.290209.x
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of the school dental screening programme in stimulating dental attendance for children in need of treatment in Northern Ireland

Abstract: School dental screening was capable of stimulating dental attendance. The strong effect among the lowest socio-economic group shows that school dental screening may be used to decrease dental health inequalities.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
20
0

Year Published

2003
2003
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(21 citation statements)
references
References 0 publications
1
20
0
Order By: Relevance
“…For 6‐year‐old children, a screening conducted in 1994–1995 in the whole Département of Val d'Oise revealed that 44.6% of the same‐aged children in the first town and 55.8% in the second town had dental caries experience (10), compared with 51% overall in the present study (44% in the first town and 59% in the second one). The response rate for the questionnaires (77%) was equivalent to that obtained in other similar studies (13), and was considered good. The children of families that did not reply to the questionnaire ( n = 60) had higher caries experience ( P < 0.05).…”
Section: Discussionsupporting
confidence: 64%
“…For 6‐year‐old children, a screening conducted in 1994–1995 in the whole Département of Val d'Oise revealed that 44.6% of the same‐aged children in the first town and 55.8% in the second town had dental caries experience (10), compared with 51% overall in the present study (44% in the first town and 59% in the second one). The response rate for the questionnaires (77%) was equivalent to that obtained in other similar studies (13), and was considered good. The children of families that did not reply to the questionnaire ( n = 60) had higher caries experience ( P < 0.05).…”
Section: Discussionsupporting
confidence: 64%
“…Furthermore, dental screening at schools, performed by dentists participating in the program, helps with the detection of normative dental treatment needs that are often not detected by the guardians [14]. Similar programs have been developed in the UK and India demonstrating that the active search for cases of diseases in schools encourages access to dental care and awareness of both parents and children of the need for this, especially among low-income groups [58,59]. Therefore, health programs such as PAS, based on healthy alliances, and targeting resources to areas of greatest social exclusion are an essential requirement for tackling the oral health inequalities of children [60].…”
Section: Discussionmentioning
confidence: 99%
“…These factors might be the socioeconomic and psychological status of parents, difficulties in booking a consultation or transportation, fear of the dentist, and oral health myths [17,18]. In this sense, more important than use this information to preview and planning the health services in dental clinic schools is to understand this reality as a peculiar one, that demands a better comprehension by professors and students [18,19,20,21].…”
Section: Discussionmentioning
confidence: 99%